2017
DOI: 10.3847/1538-4357/aa5f5c
|View full text |Cite
|
Sign up to set email alerts
|

The Limited Impact of Outflows: Integral-field Spectroscopy of 20 Local AGNs

Abstract: To investigate AGN outflows as a tracer of AGN feedback on star-formation, we perform integral-field spectroscopy of 20 type 2 AGNs at z<0.1, which are luminous AGNs with the [O III] luminosity >10 41.5 erg s −1 , and exhibit strong outflow signatures in the [O III] kinematics. By decomposing the emission-line profile, we obtain the maps of the narrow and broad components of [O III] and Hα lines, respectively. The broad components in both [O III] and Hα represent the non-gravitational kinematics, i.e., gas … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
112
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(128 citation statements)
references
References 64 publications
13
112
3
Order By: Relevance
“…The difference is noticeable in the case of composite objects as expected since the contribution from non-AGN, i.e., SF region, is most significant compared to Seyfert galaxies and LINERs. While the limitation of this work is the lack of spatial resolution, Karouzos et al (2016); Bae et al (2017) used a subsample of AGNs with strong outflow signatures in [O iii] to obtain integral field spectroscopy data. By applying the same kinematic analysis with double Gaussian models adopted in this paper to each pixel in the outflow region, they found that both narrow and broad components of [O iii] are presenting non-viral outflow kinematics.…”
Section: Comparison Of Hα Kinematics With [O Iii]mentioning
confidence: 99%
“…The difference is noticeable in the case of composite objects as expected since the contribution from non-AGN, i.e., SF region, is most significant compared to Seyfert galaxies and LINERs. While the limitation of this work is the lack of spatial resolution, Karouzos et al (2016); Bae et al (2017) used a subsample of AGNs with strong outflow signatures in [O iii] to obtain integral field spectroscopy data. By applying the same kinematic analysis with double Gaussian models adopted in this paper to each pixel in the outflow region, they found that both narrow and broad components of [O iii] are presenting non-viral outflow kinematics.…”
Section: Comparison Of Hα Kinematics With [O Iii]mentioning
confidence: 99%
“…Green-dots present the results from Karouzos et al (2016a). The measured values from Bae et al (2017) Husemann et al (2014) and Bae et al (2017) . ized gas emissions are aligned, the radio jets may be responsible for driving outflows and shock ionization, hence driving the correlations between radio emissions and gas kinematics (e.g., Veilleux 1991;Bower et al 1995;Zakamska & Greene 2014). In a radio-loud AGN 4C12.50 fast outflows in HI gas are detected with an extremely blue-shifted velocity, ∼1000 km s −1 relative to the systematic velocity at the location of the southern jet.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 8 we compare the measured NLR size based on [O III] with the [O III] luminosity for our sample, combined with various AGNs selected from literature, for which the photoionization size was measured with a consistent manner (Husemann et al 2013(Husemann et al , 2014Karouzos et al 2016a;Bae et al 2017). Note that since all these measures are dust-uncorrected [O III] luminosity, we use [O III] luminosity without correcting for dust obscuration.…”
Section: Agn-photoionisation Sizementioning
confidence: 99%
See 2 more Smart Citations